Vertical Integration in the Poultry Industry: Why Different Governance Structures? - Similä, Jan Ole (2014)
Vertical integration and vertical coordination are terms used to describe the poultry industry. An integration strategy is described as complex with many different parameters in play. A major argument for vertical integration in the poultry industry is the economic argument - scale and margin control. When we look into the industry we find there are relatively large variations from total vertical integration to market based organization. The large variations make it difficult to see how you can promote consistent economic arguments as justification for decisions. Institutional economic theory acknowledges, however, that decisions can be influenced by the institutional environment. Institutions are essentially rules of conduct, and as such it should to some extent be possible to predict the decisions, if you have good knowledge of the main institutions. National or regional cultural characteristics represent in this respect an interesting institution. In this article we will discuss culture as a possible explanation for the variations in degree of vertical integration in the poultry industry.